Improved oral absorption and anti-lung cancer activity of paclitaxel-loaded mixed micelles. (1st January 2017) - Hou, Jian; Sun, E.; Zhang, Zhen-Hai; Wang, Jing; Yang, Lei; Cui, Li; Ke, Zhong-Cheng; Tan, Xiao-Bin; Jia, Xiao-Bin; Lv, Huixia
Abstract: The aim of this study was to establish a paclitaxel (PTX)-loaded mixed micelle delivery system (PTX-TP-M) with vitamin E-TPGS (TPGS) and Plasdone®S-630 Copovidone (PVPS630) as carriers to improve the solubility, oral absorption, and anti-tumor activity of PTX against lung cancer. In this study, PTX-TP-M was prepared using the ethanol thin-film dispersion method followed by characterization of the binary mixed micelles system. The average size of the PTX-TP-M was 83.5 ± 1.8 nm with a polydispersity index of 0.265 ± 0.007 and the drug loading (DL%) and entrapment efficiency (EE%) were 3.09 ± 0.09% and 95.67 ± 2.84%, respectively, which contributed to a high solubility of PTX about 24947-fold increase in water (4.78 ± 0.14 mg/mL). In addition, TEM analysis showed that the PTX-TP-M appeared spherical in structure and was well dispersed without aggregation and adhesion. In vitro release studies showed that the PTX-TP-M displayed a sustained release compared to free PTX in the dialysis bag. The efflux ratio of PTX reduced from 44.83 to 3.52 when formulated as PTX-TP-M; a 92.15% reduction, studied using the Caco-2 monolayer model. The oral bioavailability of PTX also improved by 4.35-fold, suggesting that PTX-TP-M can markedly promote the absorption in the gastrointestinal tract. Using in vitro MTT assays, it was observed that cytotoxicity was markedly increased, and IC50 values of PTX-TP-M (3.14 ± 0.85 and 8.28 ± 1.02 μg/mL) were lower than those of PTX solution (5.21 ± 0.93 and 14.53 ± 1.96 μg/mL) in A549 and Lewis cell, respectively. In vivo anti-tumor studies showed that PTX-TP-M achieved higher anti-tumor efficacy compared with PTX in Lewis bared C57BL/6 mice. Furthermore, a gastrointestinal safety assay also proved the safety of PTX-TP-M. All results demonstrated that the PTX-TP-M exhibited great potential for delivering PTX with increased solubility, oral bioavailability, and anti-cancer activity and this binary mixed micelles drug delivery system has potential to be used clinically.